Bioelectrochemically functional nanohybrids through co-assembling of proteins and surfactants onto carbon nanotubes facilitated electron transfer of assembled proteins with enhanced faradic response - Yan, Yiming (Langmuir : the ACS journal of surfaces and colloids, 2005)
Preparation and bioelectrochemical properties of functional nanohybrids through co-assembling of hemeproteins (i.e., horseradish peroxidase, hemoglobin, myoglobin and cytochrome c) and surfactants onto carbon nanotubes (CNTs) are described. The prepared protein-surfactant-CNT nanohybrids are found to possess facilitated interfacial electron transfer of the proteins with enhanced faradic responses. The enhancements are ascribed for the first time to the properties of the surfactants for facilitation of protein electrochemistry and the improved portion of electroactive proteins assembled, of which the latter assignment is closely associated with the electrochemical and structural properties of the nanotubes and the three-dimensional architecture of the CNT film confined onto the glassy carbon electrode. It is proposed that the single and/or small bundles of the nanotubes in the CNT film electrode can be rationally functionalized with surfactants to be functional nanoelectrodes capable of facilitating electron transfer of proteins. The three-dimensional confinement of these functional nanowires onto the GC electrode essentially increases the portion of electroactive proteins assembled in the nanohybrids. These properties of the protein-surfactant-CNT nanohybrids, combined with the bioelectrochemical catalytic activity, could make them useful for development of bioelectronic devices and investigation of protein electrochemistry at functional interfaces